The effect of various concentrations of HA-TCP derived from cockle shell synthesis on scaffold porosity - Reyhan Alvaryan Ferdynanto; Priska Evita Setia Dharmayanti; Putu Tahlia Krisna Dewi; Widyasri Prananingrum (Dental Journal (Majalah Kedokteran Gigi), 2018)
Background: Porosity is an important property that must be possessed by scaffold due to its role in new bone growth. Hydroxyapatite is a scaffold material with a composition resembling that of bone that can be synthesized from cockle shell (Anadara granosa). Purpose: This research aimed to determine the effects of various HA-TCP concentrations (wt%) derived from cockle shell synthesis on scaffold porosity. Methods: HA-TCP was synthesized from cockle shells using a hydrothermal method at 200o C with a 12-hour sintering process period. An XRD test was subsequently carried out to determine the composition of hydroxyapatite (HA) and tricalcium phosphate (TCP) compounds. Eighteen scaffold samples (n=6) were then produced using a freeze dry method and divided into three groups, namely; Group 1 (K1) treated with 5% HA-TCP, Group 2 (K2) treated with 25% HA-TCP and Group 3 (K3) treated with 50% HA-TCP. Thereafter, a scaffold porosity test was conducted using liquid displacement method. Scaffold porosity was observed by means of an SEM image. A One-Way ANOVA test was subsequently performed, followed by an LSD Post-Hoc test (p <0.05). Results: The results of the XRD test showed that the percentage of HA was 51.5%, while TCP was 16.8%. The porosity of the scaffolds was within the range of 67.24% - 80.17%. The highest porosity was found in Group 1, while the lowest occurred in Group 3. There were significant differences in all groups. Conclusion: The concentration of HA-TCP derived from the synthesis of cockle shells affects the porosity of scaffold. The lower the concentration of HA-TCP, the higher the scaffold porosity.